Pengembangan Sensor Elektrokimia Berbasis Material Nano untuk Deteksi Ion Timbal (Pb²⁺) Menggunakan Sistem Elektronika Terintegrasi - Rahmawati, Asde; Nurjanah, Siti; Fahrizal, Fahrizal; Marta Putri, Dila; Ikhsan, M; Wajhi Akramunnas, Bastul (Fakultas Teknik UMRI, 2025)
Electrochemical sensors are a reliable method for detecting the presence of heavy metal ions such as lead (Pb²⁺) in aquatic environments. In this study, a sensor was developed based on a carbon paste electrode modified with ZnO nanomaterials and polyaniline, and integrated with a data acquisition system using a microcontroller. Voltammetric characterization results showed that the sensor could detect Pb²⁺ with high sensitivity at low concentrations. This system is expected to be applied for real-time and portable water quality monitoring.